Frequency of CYP2D6*3 Allele in Macedonian Population - Pilot Study - Krstevski, Gregor; Senev, Aleksandar; Kirijas, Meri; Petlichkovski, Aleksandar (My University, 2011)
Background. The cytochrome P450 enzymes are members of an isoenzyme superfamily that catalyzes the oxidation of many drugs and chemicals. Genetic polymorphisms have been identified for some of the CYP450 enzyme genes that alter enzyme activity. Depending on gene variations, individuals may be intermediate metabolizers (IMs) or poor metabolizers (PMs) or ultra-rapid metabolizers (UMs). CYP2D6 is responsible for the metabolism of environmental chemicals and drugs such as: antiarrhythmics, adenoreceptor antagonists and tricyclic antidepressants. Methods: Thirty-eight volunteers of Macedonian origin previously involved in pahrmacokynetic studies at the institute of Pharmacology and Toxicology were recruited for this study. After signing written consent, DNA was isolated using the phenol-chlorophorm procedure and stored at the human DNA bank (hDNAMKD) at the Institute of Immunobiology and Human Genetics. The exon 5 of the CYP2D6 gene was PCR amplified in order to confirm the presence of the allele # 3 of the 2D6 gene. The resulting product was then digested with the enzyme MspI. Next, electrophoretic separation on the Multiphor II using 12.5% polyacrilamide gel and silver staining was performed. Results: The results indicated that of the 38 samples analyzed with the polyacrylamide gel electrophoresis, 37 portrayed a normal homozygote genotype while only 1 sample showed heterozygous genotypic pattern. Therefore, the frequency of 2D6*3 heterozygotes in the 38 studied samples is 2.6%. This finding is comparable with the other European populations upon which this study has been done. Conclusion: To our knowledge, this is the first study analyzing genetic polymorphism of the CYP2D6 gene in the Macedonian population. In this study we present preliminary results, with the goal to continue and eventualy analyze a representative number of samples which would make comparisons with other European populations possible.
Keywords: CYP2D6*3, genetic polymorphism, PCR, RFLP, polyacrileamide gel, Macedonian population.